Funscience Methods to Improve Student Activeness in Science Learning - Dytchia Septi Kesuma; Zakirman Zakirman; Ade Usra Berli; Mira Meilisa; Chichi Rahayu (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The new challenge faced in carrying out IPA learning in elementary school, especially in SDN 01 Kubang Siamang Bunyi is to increase student activeness and involvement. The aim of this research is to improve student liveliness and engagement through Funscience methods in IPA learning. Fun science is a method by using simple experiments that are interestingly packaged and cause fun effects for students in IPA learning. This type of research is descriptive, involving student respondents in SDN 01 Kubang Siamang Bunyi Regency 50 cities of West Sumatra Province. Data collection instruments in the form of observation sheets and interviews. Data is analyzed descriptively. The results of the data analysis showed that the application of Funscience methods improved the activeness of students in IPA learning in SDN 01 Kubang Siamang Bunyi Kenagarian Kubang Regency 50 City. Funscience can be one of the alternative methods that can be applied in IPA learning to improve and improve the quality of learning. Funscience is a method of learning that has been adapted to the characteristics of students in elementary school.